UPAYA PENINGKATAN KEDISIPLINAN SISWA DI WATNATHAM ISLAM SCHOOL PANARE PATTANI-THAILAND SELATAN - Azizah, Nadia Nur (EDUKASIA, 2019)
Student discipline is one of the internal factors to achieve learning objectives. Discipline is formed because of the influence of the culture of the surrounding environment over a long period of time consistently and continuously. Watnatham Islam School uses two types of curriculum, which are Islamic and academic curriculum. It influences the culture of discipliness in schools and boarding schools. This study aims to (1) describe the level of discipline of students and (2) describe school efforts to improve student discipline in the academic curriculum learning process and Islamic curriculum at high Mattayom Watnatham Islam School Panare Pattani-South Thailand on 2018-2019. This research is a qualitative research with field research as the method. Data was collection using (1) interviews, (2) observations, and (3) documentation. The analysis technique used in this study is a data analysis technique developed by Miles, Huberman and Saldana, which consist of data collection, condensation data, data display, conclusion drawing and verification